Answer:
xyz plz my answer as brainliest
It's said "The value √-9 is not -3 because --------------------
So you need to prove why -3 is not the value of √-9.
As you know (-3)^2 = (-3) * (-3) = 9, ≠ -9
Answer is A.
(-3)^2 ≠ -9
Answer:
∠A = ∠D (**but very important Δ ABC has to be congruent to Δ DEF)
Step-by-step explanation:
It will help if you draw the triangles out and label the same sides. Then according to the side-angle-side (SAS) rule, ∠A should be equal to ∠D
Answer:
3
Step-by-step explanation:
-m+8=4m-7
8=4m-(-m)-7
8=4m+m-7
8=5m-7
5m=8+7
5m=15
m=15/5
m=3
What two factors of 48 add up to -16? -4 and -12
So the factored form would be (x-4)(x-12)